Sinter-joining of two different bioceramic materials - Sarah Nistler; Christoph Hofstetter; Stefan Baudis; Martin Schwentenwein; Jürgen Stampfl (Open Ceramics)
In this study, we successfully created an implant to mimic natural bone by combining a load-bearing shell made of zirconia (cortical bone) with an osteoconductive filling made of hydroxyapatite (cancellous bone). Using additive manufacturing, both parts were produced separately followed by a sinter-joining process to form one hybrid final part. We first tested the sinter-joining process on a simple ring-in-ring design, creating a defined press-fit between the outer and inner ring. We also introduced sinter supports to ensure excellent alignment and manufactured biaxial bending plates to test the mechanical resistance. We found a significant increase in the maximal measured force from (72±53) N to (366±88) N for a 5 % and 10 % press-fit, respectively. Furthermore, we successfully manufactured a more complex bone implant with this sinter-joining method.